Histological digestive tract of milkfish’s (Chanos chanos Forskal.) from District Ujung Pangkah, Gresik - Ummul Firmani; Aminin Aminin (Kontribusia : Research Dissemination for Community Development, 2021)
Milkfish is a commodity with a high production rate. From the milkfish commodity, Gresik is the center of fishery production in East Java. Milkfish belongs to the herbivore group with the type of food from the plant group. Milkfish cultivation in traditional ponds still uses natural food as the main food for the cultivated commodities. Fish food affects the structure of the digestive tract, especially the intestines of fish. herbivorous fish have very long intestines even many times the body length, compared to omnivorous and carnivorous fish. Thus, this study aims to find out more clearly about the structure of the milkfish gut tissue. The digestive tract is related to the process of digestion, absorption and disposal of food waste, so it has an important role in the growth of fish. The research method used was descriptive experimental by making preparations of fish intestinal tissue and staining with Hematoxylin Eosin. The intestines of the fish observed were the front, middle and back. Observation of the preparations using a microscope with a dot slide scan photo. From the results of the study obtained an overview of the intestinal tissue structure of the upper (proximal), middle (middle) and lower (distal) fish. The structure of the front, middle and back of the milkfish gut tissue is similar, the difference lies in the number and thickness of the villi.